Frying Time and Temperature Conditions’ Influences on Physicochemical, Texture, and Sensorial Quality Parameters of Barley-Soybean Chips - Huda Abdalrahman AL Jumayi; Amira M. G. Darwish (Journal of Food Quality)
Demand for innovative healthy snacks that achieve consumer satisfaction represents increased interest for competitive food producers. The aim of this work was the assessment of physicochemical and sensory quality of barley-soybean chips involving legume protein flours by studying the effects of different substitution levels (10, 20, and 30%) of defatted soybean (DSB) flour, frying temperatures (150, 170, and 190°C), and frying times (60, 90, and 120 sec). The chips’ moisture content was significantly decreased with increased frying temperature and time. The moisture content (1.40%) was achieved at 10% DSB fried at 190°C for 120 sec. The least absorbed oil (29.25%) was achieved at the least substitution percentage (10% DSB), the least frying temperature (150°C), and the least frying time (60 sec). These results were reflected on sensorial parameters that revealed that the most preferred chips were barley-soybean chips with 10% DSB fried at 150 and 170°C. The amylose content was increased by 33.80% in chips substituted with 30% DSB, while it was decreased to 27.16% in chips substituted with 10% DSB, and vice versa for the amylopectin content. TPA revealed that DSB substitution levels were directly proportional with hardness and inversely proportional with elasticity and adhesiveness. From obtained results, substitution levels with 10% DSB fried at 150°C are recommended. These findings encourage the production of innovative enhanced snacks involving legume protein while maintaining consumer satisfaction.